The earliest fossil record of true crickets belonging to the Baissogryllidae (Insecta, Orthoptera, Grylloidea). (8th March 2019) - Wang, H.; Fang, Y. N.; Fang, Y.; Jarzembowski, E. A.; Wang, B.; Zhang, H. C.
Abstract: Baissogryllidae is an extinct family of the insect superfamily Grylloidea, previously known from Late Jurassic – Early Cretaceous time. A new genus and species, Sinagryllus xinjiangensis gen. et sp. nov., is described here based on a well-preserved forewing from the Lower Jurassic Sangonghe Formation of Xinjiang, northwestern China. It can be attributed to Baissogryllidae based on the combination of the following characteristics: a true mirror in the male tegminal stridulatory apparatus; and a distinct widening of the area between CuA2, lateral part of the diagonal vein, and proximal part of the proximal branch of MP+CuA1 . This find represents not only the earliest record of Baissogryllidae, but also the first fossil wing of Grylloidea reported from China.